2005
DOI: 10.1088/0022-3727/38/3/010
|View full text |Cite
|
Sign up to set email alerts
|

Generation of ozone by pulsed corona discharge over water surface in hybrid gas–liquid electrical discharge reactor

Abstract: Production of ozone generated by the gas phase pulse positive corona discharge above water was investigated for different discharge gap spacing (2.5-10 mm), applied input power (2-45 W), and gas composition (oxygen mixtures with argon or nitrogen). Ozone concentration increased with increasing power input and with increasing discharge gap. The production of ozone was significantly affected by the presence of water vapor formed through the vaporization of water at the gas-liquid interface by the action of the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
117
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(118 citation statements)
references
References 53 publications
0
117
0
1
Order By: Relevance
“…5 However, the rate and efficiency of H 2 O 2 formation is not necessarily dependent on the electrode material. 6 Another efficient strategy which can be applied to enhance the generation of active species and the consequent pollutant degradation is the combination of non-thermal plasma reactors with different advanced oxidation processes, such as ozonation, 7 TiO 2 photo-catalysis, [8][9][10] alumina and silica gel (resulting in adsorption) 11 and homogeneous (e.g., Fe…”
Section: Introductionmentioning
confidence: 99%
“…5 However, the rate and efficiency of H 2 O 2 formation is not necessarily dependent on the electrode material. 6 Another efficient strategy which can be applied to enhance the generation of active species and the consequent pollutant degradation is the combination of non-thermal plasma reactors with different advanced oxidation processes, such as ozonation, 7 TiO 2 photo-catalysis, [8][9][10] alumina and silica gel (resulting in adsorption) 11 and homogeneous (e.g., Fe…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have utilized pulsed gas phase discharges generated over a water surface to produce in the gas or at the gas-liquid interface strongly oxidative species, such as OH radicals, O atoms, ozone (O 3 ) and hydrogen peroxide (H 2 O 2 ) [16,19,24,25]. Due to the microsecond lifetime of radicals such as OH and O, only O 3 and H 2 O 2 , produced above the water surface (in the gaseous phase), can diffuse into the aqueous phase.…”
Section: Introductionmentioning
confidence: 99%
“…The phenol decomposition rate at 60 min is greatest (56%) in pure O 2 , it has the second highest value (42%) in pure N 2 , and lesser values (under 40%) are obtained in other N 2 -O 2 mixtures. When N 2 -O 2 is used as the background gas, the following reactions can be induced in a pulsed discharge plasma [5,[7][8][9][10]12]:…”
Section: Influence Of Charging Voltage and Number Of Needle Electrodementioning
confidence: 99%
“…Kuroki and colleages [4] generated pulsed discharge plasma above an aqueous phenol solution with air, Ar, and H 2 O 2 gas sparging and described the reactions in the plasma in the case of each sparging gas. Lukes and colleagues [5] generated pulsed discharge plasma above water in the air and reported that oxidizing agents such as OH, O 3 , O, and H 2 O 2 were produced in the plasma. Furthermore, they reported that OH radicals were also produced by the reaction between H 2 O vapor and nitrogen molecules excited in the metastable state [hereafter described as N 2 (A)].…”
Section: Introductionmentioning
confidence: 99%